Identifying Tensions in the Use of Open Licenses in OER Repositories - Amiel, Tel; Soares, Tiago Chagas (International Review of Research in Open and Distributed Learning, 2016)
We present an analysis of 50 repositories for educational content conducted through an "audit system" that helped us classify these repositories, their software systems, promoters, and how they communicated their licensing practices. We randomly accessed five resources from each repository to investigate the alignment of licensing information between the resources themselves, metadata pages and overall site policies. We identified a high level of incongruity that could lead to a limited impact in OER use and reuse. We discuss the lack of guidance in implementation of such repositories, particularly to those who do not have wide institutional support to implement such systems. We finalize with a critical discussion on the emphasis given to licensing in the OER movement, and how it may be an evidence of a clash between the social and legal commons.